A descriptive survey of cancer helplines in the United Kingdom: Who they are, the services offered, and the accessibility of those services. Issue 8 (17th November 2016) - Leydon, Geraldine M.; Stuart, Beth; Danquah, Lisa; Ekberg, Katie; Brindle, Lucy; Latter, Sue; Moynihan, Clare; Salmon, Peter; Howe, Sonia; Stokoe, Elizabeth; Little, Paul
Abstract: Background: There are more than 1500 UK health helplines in operation, yet we have scant knowledge about the resources in place to support the seeking and delivering of cancer‐related telephone help and support. This research aimed to identify and describe cancer and cancer‐related helpline service provision: the number of helplines available, the variety of services provided, and the accessibility of those services. Method: This study used online national questionnaire survey sent to 95 cancer and cancer‐related helplines in the United Kingdom. Results: A total of 69 (73%) of 95 surveyed cancer and cancer‐related helplines completed the survey. Most helplines/organizations were registered charities, supported by donations; 73.5% of helplines had national coverage. Most helplines served all age‐groups, ethnic groups, and men and women. Only 13.4% had a number that was free from landlines and most mobile networks, and 56.6% could only be contacted during working hours. More than 50% of helplines reported no provisions for callers with additional needs, and 55% had no clinical staff available to callers. Ongoing support and training for helpline staff was available but variable. Conclusion: Although cancer helplines in the United Kingdom offer reasonably broad coverage across the country, there are still potential barriers to accessibility. There are also opportunities to optimize the training of staff/volunteers across the sector. There are further prospects for helplines to enhance services and sustain appropriate and realistic quality standards.